Risks and Countermeasures of Personal Information Processing in Minors’ Network Socialization - Huiyi Zhu (Law and Economy, 2025)
Minors experience network cognition, network imitation and network interaction in the algorithmic society. The invisible hand of algorithm is inseparable from every network action. When minors encounter algorithmic recommendation services on social media, their personal information is abused by the algorithm. The existing regulations for the protection of personal information based on algorithms have some problems, such as rigid age division of notification and consent mechanism and one-time notification and consent. In this regard, it is necessary to re-establish the risk assessment system for minors’ personal information, improve the operability of consent notification and emphasize dynamic notification, balance the rights and interests of minors’ personal information and the freedom of expression on the Internet, and build an algorithmic society for minors to communicate and trust.